Application of benthic macroinvertebrates as potential bio-indicators in Malaysian's rivers: gap and bibliometric analyses - Hettige, Nadeesha Dilani; Hashim, Rohasliney; Abas Kutty, Ahmad (Malaysian Abstracting and Indexing System, 2024)
The literature on reliable indices, suitable bio-indicators, taxonomic level, frequency of measurements, and replications on benthic macroinvertebrates remains scarce in Malaysia. In addition, no review study was conducted using bibliometric analysis related to this discipline. Thus, this review aimed at gap and bibliometric analysis of publications on benthic macroinvertebrates as potential biological indicators. Sixty-six relevant scientific research papers from 2011 to 2022 were selected from the different databases. Then, descriptive and inferential statistical analyses were performed to assess the most reliable potential bio-indicators for river assessment and monitoring. Visualized statistics regarding bibliographic coupling analysis of authors, journal proceedings, and organizations were analyzed. The findings revealed that publications on invertebrates had no significant relationship in the last ten years (r = 0.241; p > 0.05). Most publications on macroinvertebrates in Malaysian rivers were found in the Scopus database (53.57%). Therefore, research articles must be published in journals included in the Journal Citation Report (JCR) to improve their quality further. Besides, benthic macroinvertebrates are commonly identified only up to the family level (47%) due to incomplete tropical benthic macroinvertebrates identification keys. As such, using environmental DNA methods with the power of next-generation sequencing has come in handy in bioindicator species identification. Among the potential bio-indicators found in Malaysian rivers are Chironomidae (9.11%), Baetidae (8.87%), and Hydropsychidae (8.62%). Based on the approaches utilized in analyzing benthic macroinvertebrates as bio-indicators, in-depth research such as bioassay and toxicology tests are necessary to realize the potential bio-indicators fully. Many studies focused on recreational rivers in Peninsular Malaysia. Therefore, research studies will be expanded to include urban rivers and rivers in Sabah and Sarawak. Also, to overcome the limitation of the single biotic index, developing a multimetric index to evaluate the water quality by selecting many river basins is essential. Bibliographic analysis showed that the Institute for Tropical Biology and Conservation, Universiti Malaysia Sabah, made the greatest total link strength. The Serangga Journal published the highest number of research articles. Finally, utilizing advanced technologies is recommended to address Malaysia's lack of potential bio-indicator studies